OPTIMASI POLA PEMANFAATAN LAHAN USAHATANI YANG BERWAWASAN LINGKUNGAN DI DAERAH TRANSMIGRASI UPT LALUNDU KABUPATEN DONGGALA - Nur, Muh Ikhsan (AGROTEKBIS, 2015)
The research aimed at (1) knowing the usage pattern suitability of agricultural business land at the transmigration area (2) knowing the agricultural business branch that can be done to reach maximum production and income level (3) knowing the optimum usage alternative by still keeping the living environment preservation. The research was done in 4 month, from May to September 2004 in Transmigration Settlement Unit (UPT) of Lalundu of Donggala Regency, Central Sulawesi Province. Based on the analysis results, it could be concluded (1) there were 15 agricultural businesses that possible to do at the agricultural land at the Lalundu UPT, paddy-paddy, paddy-soybean, paddy-green pea-, paddy-ground nut, paddy-corn, paddy-paddy-soybean, paddy-paddy-corn, coconut, cacao, coffee, corn-coffee, coconut cacao, (2) the usage pattern of agricultural business land was not optimal yet. The agricultural business income contribution in 2014 was Rp 410.635.000,-. The value was obtained from the business of eight commodity types, that were paddy, soybean, green pea, ground nut, corn, coconut, cacao and coffee (3) from the 15 agricultural business activities patterns, there were six optimal pattern with maximum income contribution of Rp 6363561.000,-. The value increase about Rp 225.926.000,- (35%) from the income of 2013 (4) various activities done by transmigration people have given positive and negative impacts to the environment. From the activities, the positive impacts were greater (with score of 41) than the negative one (with score of 9). It showed that the agricultural business pattern still can be improved and get optimum income.